Hubungan antara Dukungan Sosial Orang Tua dan Grit pada Siswa TNI di Lembaga ‘X’ Kota Bandung - Nila Kencana Tanjung; Lisa Imelia Satyawan (Universitas Kristen Maranatha, 2021)
The purposeof this study is to determine relationship between social support from parents and grit in 96 soldier students of “X” institution Bandung. The research method used is correlation. Quesionnaire of social support based on Sarafino’s theory (2002). Quesionnaire of grit were developed by Dr. Irene Prameswari Edwina, M.Si., Psikolog dan Ni Luh Ayu Viviekananda, M.Psi., Psikolog based on grit theory (Duckworth,2016). Data obtained were process educing Spearman correlation with SPSS 20 program. Validity of social support from parent scale range between 0,274 to 0760 and reliability is 0,900. Validity of grit scale range between 0,44 – 0,95 and reliability is 0,89. Based on statistical data processing, each form of social support from parents (information, appraisal, instrumental, and emotional support) were correlated significantly with grit (each coefficient r=0546, r=0,597; r=0,409; r=0,434). Conclusion of this research is that there is a significant positive relationship between each form of social support from parents. The results showed that there was a relationship between each form of social support relationship between parents and grit. The appraisal support has a relationship with grit with a coefficient value of r = 0.597, information support has a relationship with grit with a coefficient value of r = 0.546, emotional support has a relationship with grit with a correlation coefficient value r = 0.434, instrumental support has a relationship with grit with a coefficient of r = 0.409. Keywords: Grit, Social Support from Parents, TNI student